Transitioning of special needs paediatric patients to adult special needs dental services. (22nd July 2014) - Borromeo, GL; Bramante, G; Betar, D; Bhikha, C; Cai, YY; Cajili, C
Abstract Background Special needs dentistry is in its infancy compared to other dental specialties. Continuity of care through transition from paediatric to adult dental care providers is unknown. This study seeks to determine the nature of transition practices adopted by paediatric and special needs (SN) specialists practising throughout Australia. Methods A survey was sent to all paediatric and SN specialist dentists in Australia to determine the nature of current transition practices for paediatric SN patients in Australia. Two subsequent mail‐outs were sent to non‐responders. Results Forty‐nine specialist dentists registered across Australia completed the survey, of which 35 (71%) were paediatric dentists and 14 (29%) were SN dentists. Both paediatric and SN dentists treated patients over the age of 18. Of the total paediatric dentists who had transition discussions with their paediatric patients and their families, the majority (over 80%) discussed treatment options available as part of future oral care management. Paediatric dentists identified level of independence and financial situations as the most significant barrier for transition. Conclusions Key factors exist that should be discussed with SN patients and their parents and/or guardians in order to enhance the prospect of sustained dental care into adulthood.